Sustainability : life chances and livelihoods - Redclift, Michael, 1946- (Routledge, 1999)
Sustainability: Life Chances and Livelihoods shows that the scope of sustainability thinking needs to be widened to embrace public policies and experiences in both developed and developing countries.